Error control in FORM reliability analysis - Gallimard, Laurent (European Journal of Computational Mechanics, 2012)
This paper deals with the failure probability error induced by the coupling between the first-order reliability method (FORM) and the Finite Element Method (FEM). A FEM error estimator based on the concept of error in constitutive relation associated with goal-oriented error estimation is proposed. Furthermore an importance sampling technique is used to compute the error due to the FORM approximation. Both these errors are used to choose a finite element mesh adapted to the problem.